Ethiopia [in Strategies and priorities for African agriculture] - Diao, Xinshen; Taffesse, Alemayehu Seyoum; Dorosh, Paul A.; Thurlow, James; Nin-Pratt, Alejandro; Yu, Bingxin (International Food Policy Research Institute, 2012)
Agriculture is perhaps the most important economic sector for sustainable development and poverty reduction in Ethiopia. More than 85 percent of the population live in rural areas and depend crucially on agriculture for their livelihoods. The sector also accounts for more than 40 percent of national gross domestic product (GDP) and 90 percent of exports, and it provides basic needs and income to more than 90 percent of the country’s poor population. In recent years the agricultural sector has driven economic growth in the overall economy while also improving food security and reducing poverty (World Bank 2007).